EVALUASI DAN PERANCANGAN SISTEM PENGENDALIAN INTERN PENJUALAN JASA HOTEL (Studi Kasus Pada Bandung Giri Gahana Golf and Resort): EVALUASI DAN PERANCANGAN SISTEM PENGENDALIAN INTERN PENJUALAN JASA HOTEL (Studi Kasus Pada Bandung Giri Gahana Golf and Resort) - Ari Permana; Sugih Sutrisno Putra; Dian Imanina Burhany (Jurnal Akuntansi Bisnis dan Ekonomi, 2020)
The sale of services is a determining factor in the leisure business, because it is the company's main source of income. In order for maximum income to be obtained, an effective and efficient Internal Control System (SPI) is needed to reduce fraud that occurs in the company so that revenue can be maximized. SPI at Bandung Giri Gahana Golf & Resort is still ineffective because it lacks supervision and does not implement Standard Operating Procedures (SOP) by the frontliners. Therefore it is necessary to conduct an evaluation to assess how effective and efficient the existing SPI is and what recommendations are needed to improve it. This study aims to evaluate and analyze and design SPI at Bandung Giri Gahana Golf & Resort. The research was conducted using a qualitative descriptive method with a case study approach. Data collection was carried out by documentation, observation and interviews.